2002
DOI: 10.2337/diacare.25.11.1914
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a Homogeneous Assay With a Precipitation Method for the Measurement of HDL Cholesterol in Diabetic Patients

Abstract: OBJECTIVE -To compare direct-measured HDL cholesterol with HDL cholesterol measured by a precipitation method. RESEARCH DESIGN AND METHODS-We compared a homogeneous assay for direct HDL cholesterol analysis with the phosphotungstic acid magnesium chloride precipitation method in 55 type 1 diabetic patients, 70 type 2 diabetic patients, and 82 nondiabetic normal control subjects with plasma triglyceride levels Ͻ4.6 mmol/l. The cholesterol content of HDL determined by the direct assay was overall 0.1 mmol/l high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
(8 reference statements)
0
4
0
1
Order By: Relevance
“…In previous studies, conventional precipitation technique was used for measuring HDL-C. It has been demonstrated that the precipitation method for HDL-C correlated well with the ultracentrifugation method but that the precipitation method exhibited a negative bias for HDL-C (Jensen et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, conventional precipitation technique was used for measuring HDL-C. It has been demonstrated that the precipitation method for HDL-C correlated well with the ultracentrifugation method but that the precipitation method exhibited a negative bias for HDL-C (Jensen et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma cholesterol levels were measured with a cholesterol assay kit from BioVision Inc (Mountain View, CA). HDL-cholesterol level was determined by phosphotungstic acid and magnesium chloride precipitation method46.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma glucose (glucose CII‐test), cholesterol (cholesterol C‐test), triglyceride (triglyceride C‐test) and phospholipid (phospholipid C‐test) were determined using an assay kit (Wako Pure Chemical Industries, Osaka, Japan). High‐density lipoprotein cholesterol was measured by phosphotungstic acid and magnesium chloride precipitation [30]. The precipitating reagent consisted of 0.55 m m phosphotungstic acid and 25 m m magnesium chloride.…”
Section: Methodsmentioning
confidence: 99%